Association of NQO1 C609T (Pro187Ser) with Risk of Oral Submucous Fibrosis in Eastern Indian Population - Mukherjee, Sanjit; Mohanty, Sweta; Katarkar, Atul; Dhariwal, Richa; Mahato, Basudev; Ray, Jay Gopal; Chaudhuri, Keya (Asian Pacific Journal of Cancer Biology, 2021)
Objective: Oral submucous fibrosis (OSF) is a debilitating disease mainly attributed to chewing areca nut with a 7.4-13% malignant transformation rate. The present study explores the role of NADPH quinone oxidoreductase 1 (NQO1) C609T (Pro187Ser) polymorphism in susceptibility to OSF among habitual areca nut chewers in an eastern Indian population. Material and Methods: In this hospital-based study, 152 controls and 179 OSF cases were genotyped at NQO1 C609T polymorphic site by PCR-RFLP and its effect on NQO1 expression in OSF tissue was studied to determine the risk of the disease. Results: Overall, about 18% of the total OSF cases were detected carrying minor TT alleles (Ser/Ser) p=0.026. When categorized by age, both CT (Pro/Ser) and TT (Ser/Ser) alleles were significantly higher (p= 0.003 & 0.004 respectively) in cases above 40years of age. NQO1 protein was 42% reduced in buccal tissues of heterozygous (Pro/Ser) carriers, whereas a 70% reduction was observed in TT (Ser/Ser) OSF cases. Conclusion: Our study suggests that the NQO1 C609T polymorphism confers increased risk for OSF in habitual chewers.